1987
DOI: 10.1037/0021-9010.72.4.567
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rater training on rater accuracy: Levels-of-processing theory and social facilitation theory perspectives.

Abstract: We use levels-of-processing theory and social facilitation theory to explain the effect of training format and group size on distance and correlation accuracy, leniency-severity, halo, retention of training and pretraining information, and subject arousal. The training factor included frame-of-reference (FOR) training, information only (INFO) training, and no training (NOT). Group size was n = 1, n = 6, and n = 12, respectively. A total of 108 subjects, randomly assigned to one of nine Training × Group Size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
4

Year Published

1992
1992
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 23 publications
4
51
0
4
Order By: Relevance
“…Several of the studies that compare rater behaviors have based those comparisons on the amount of rater experience or loose definitions of "expertise," and these studies have generally supported the notions that raters who have different amounts of experience or expertise behave differently when assigning ratings (Breland & Jones, 1984;Huot, 1988;Pula & Huot, 1993;Vaughan, 1991). A few studies have examined the association between rater characteristics and rating contexts and somewhat general measures of rating quality such as rating "accuracy" or "reliability" without focusing on specific patterns or trends in the ratings themselves, and the results of these studies support the notion that rating quality may differ when ratings are assigned by raters who have different experiences (Athey & McIntyre, 1987;Clauser, Clyman, & Swanson, 1999;Shohamy, Gordon, & Kraemer, 1992;Wolfe, 1997;Wolfe, Kao, & Ranney, 1997).…”
Section: Studies Of Raters and Rating Contextsmentioning
confidence: 97%
“…Several of the studies that compare rater behaviors have based those comparisons on the amount of rater experience or loose definitions of "expertise," and these studies have generally supported the notions that raters who have different amounts of experience or expertise behave differently when assigning ratings (Breland & Jones, 1984;Huot, 1988;Pula & Huot, 1993;Vaughan, 1991). A few studies have examined the association between rater characteristics and rating contexts and somewhat general measures of rating quality such as rating "accuracy" or "reliability" without focusing on specific patterns or trends in the ratings themselves, and the results of these studies support the notion that rating quality may differ when ratings are assigned by raters who have different experiences (Athey & McIntyre, 1987;Clauser, Clyman, & Swanson, 1999;Shohamy, Gordon, & Kraemer, 1992;Wolfe, 1997;Wolfe, Kao, & Ranney, 1997).…”
Section: Studies Of Raters and Rating Contextsmentioning
confidence: 97%
“…Using frame-of-reference training, participants review the performance of targets and then aspects of the performance central to evaluation are discussed relative to each performance dimension. Frame-ofreference training has been found to be effective in improving rating accuracy and is often the method of choice when conducting rater training (Athey & McIntyre, 1987;Roch, Woehr, Mishra, & Kieszczynska, 2012;Woehr & Huffcutt, 1994).…”
Section: Training Options To Enhance Rating Accuracymentioning
confidence: 99%
“…They concluded that rater training should emphasize observation and decision making processes rather than simply error reduction. In a laboratory study using student subjects and video-taped lectures, Athey and McIntyre (1987) showed that frame-of-reference training improved retention of information, improved accuracy, and decreased halo. A recent literature review of twenty-four rater training studies suggested the training methods best suited for reducing halo, reducing leniency, and improving accuracy .…”
Section: Rater Trainingmentioning
confidence: 99%